The causal effect of professional sports on amateur sport participation--an instrumental variable approach - Mutter, F.; Pawlowski, T. (The Free Library, 2014)
The present study provides evidence that an individually perceived relevance of professional triathlon causally increases the time spent on amateur triathlon participation. However, the transfer of these results to other countries and/or other sports is limited due to special characteristics of triathlon, such as the limited number of participants in general or the high physiological requirements.